Persons with disabilities as experts-by experience: using personal narratives to affect community attitudes in Kilifi, Kenya - Joseph K. Gona; Charles R. Newton; Sally Hartley; Karen Bunning (BMC, 2018)
Abstract Background The last decade has seen improved public awareness of disability in sub-Saharan Africa. However, negative and stereotypical views of disability still persist in many communities. We conducted a study to promote awareness of disability in rural Kenya, using a process of reflection and education. This paper reports on the second aspect - education. The research question was: How can personal narratives of living with disability affect community attitudes and responses to disability? Methods A qualitative phenomenological approach was adopted. Twenty community-based groups involving 249 participants took part. Each group participated in one focus group discussion at baseline, to explore the members' personal experiences and views of disability. The intervention involved three adults with disabilities sharing their personal narratives with each group. After the intervention, repeat focus group discussions were conducted with each group. Thematic analysis was carried out according to the framework method. Results The emergent framework consisted of four main themes, organised as opposing constructs: 'burden' and 'agency', 'sub-human' and 'human'. 'Burden' focused on the perceived hopelessness of the situation. Post-intervention revealed greater support for the 'agency' of persons with disabilities, evidenced by what the person could do, rather than their inability, and the relevance of support. The 'sub-human' to 'human' construct captured dehumanising and discriminating practice towards persons with disabilities on one side, and recognition of the person and inclusion in the community on the other. Whilst support and empathy were evident at the pre-intervention stage, post-intervention revealed greater recognition of people with disabilities as fellow human beings. Conclusion This study provides a proof of concept regarding the deployment of persons with disabilities as agents for change. Exposure to experts-by-experience provided community groups with opportunities to reflect on, examine and adjust their views on disability in this rural part of Kenya. The sharing of personal narratives appeared to resonate with group members, to encourage recognition of the person and not just the disability, and to move their resolve toward ideas for collective action. Further research is needed to assess the effects of such interventions.